Humanitarian Agenda 2015: Colombia Country Study - Minear, Larry (Tufts Archival Research Center, 2008)
Paper dated July, 2006. This case study on Colombia was undertaken as part of a larger research initiative, The Humanitarian Agenda 2015: Principles, Power, and Perceptions (HA 2015), which seeks to analyze the major challenges facing the humanitarian enterprise during the coming decade. The experience of Columbia sheds light on all four themes of the HA 2015 research. First, with respect to universality, Colombia sees itself as part and parcel of the western world. There is broad resonance between Colombian religious and civil traditions and the global humanitarian ethos, laws, and institutions. Second, he focus group and individual interviews conducted for this study concentrated on terrorism, understood as violence or the threat of violence against ordinary civilians, against their life, their property, their well-being. [Terrorism] is a means to attain a political goal which allegedly could not be attained by ordinary, lawful means, within the context of the established constitutional order.5 A broadly held consensus emerged that what might be called small t terrorism was tearing apart the human, social, economic, and political fabric of Colombian society while introducing major complications into the functioning of international and domestic humanitarian and human rights organizations. At the same time, alleged connections to an overarching global war on terrorism (capital T terrorism) were found to be overdrawn. As for the third theme, coherence, the prevailing political framework promoted by the United States government in the form of Plan Colombia and embraced by the Colombian authorities in its own democratic security policy provides an uneasy fit for international assistance and protection activities and a point of tension between the US and other donors. Finally, with regard to security, there has been by most accounts an overall reduction in the incidence of specific forms of violence in late 2005 and early 2006 from the withering levels of the preceding five years. Yet a climate of fear still pervades many sectors of society and there were, at the time of the research visit, still numerous incidents taking place, including killings and harassment of leaders of civil society organizations.